Research and evaluation of methods of regulating the modes and parameters of the selection machine - Nazarenko, I.; Slipecki, V. (Ways to Improve Construction Efficiency, 2020)
The paper deals with the study of a generalized model of a resonant vibrating machine, which fully takes into account the dynamic features of all major types of resonant machines and integrates the dynamics of two-mass resonant vibrating machines for compacting concrete mixtures. The research method envisaged the use of a discrete model of a resonant machine taking into account the concrete mixture. Concrete mixture in the equations of motion is represented by a factor that takes into account the wave phenomena .. The assumption is made that the most effective are the resonance machines that are subject to stabilization of the mode of operation over time. In this condition, it was assumed that the regulation of the working process of vibrating machines is more efficient than the mode of their operation closer to the resonance and the higher the coefficient of resonant amplification of vibrations. In order to substantiate approaches to the problem of vibration machine automation, a generalized dynamics analysis was performed, which revealed the general dynamic features of these machines. The equations of motion of the resulted model are deduced, the solution of which is obtained analytical dependences, which describe the dynamics of the resonant vibrating machine and serve as a prerequisite for the development of methods of regulation and design features of the vibrating machine. Research has identified a number of parameters that are capable of implementing the process of regulation and stabilization of the resonant mode of operation of the shock - vibrating machine. In the context of these studies, it is established that the phase angle can be a parameter for regulating and ensuring the regulation processes. It is found that the value of the phase angle decreases with increasing contact time with the vibration limiter of the vibration machine working body